Pengaruh Perendaman Serat Sabut Kelapa Pada Air Batu Kapur Terhadap Wettability - Sutrisno Sutrisno; Rudy Soenoko; Yudy Surya Irawan; Teguh Dwi Widodo (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2020)
Abstract— Processing of natural fibers as a support material for composite materials has been widely carried out. Some studies use chemicals as a medium for processing fiber while the treatment with natural ingredients has not been done much. This study discusses the ability of the matrix to penetrate the coconut fiber. Coconut fiber that has been cleaned soaked in a solution of limestone water. Immersion is done with a variation of the lime mass percentage of 0; 2.5; 5; 7.5; 10% with 8 hours soaking time. The matrix used is unsaturated polyester yucalac 157 BQTN-EX. Wettability testing by dripping a matrix on coconut fiber. Coconut coir fibers that have been dripped with a matrix in the photo to determine the contact angle. The results of measurements and observations that with variations in mass percentage of 5% limestone with an immersion time of 8 hours have a contact angle of 11O˂Φ˂31O. Immersion with a percentage of 2.5% shows the surface of the fiber has not changed. Immersion of 7.5% and 10% of the surface of the fiber has been damaged, so the matrix can not absorb the coconut fiber to the maximum. Keywords—: coconut fiber; limestone water; contact angle; wettability; SEM.